Analisis Fenomena Cancel Culture dalam Etika “Klik” Manusia di Era Digital Menurut F. Budi Hardiman - Alfredo Kevin (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
The research of this study pays attention to the cancel culture phenomenon in the ethics of human communication in today’s digital era. In particular, the author will describe F. Budi Hardiman’s thoughts on the ethics of “Click” in human existence in cyberspace. The methodology used in this research is qualitative-descriptive. Cancel culture is a phenomenon that has recently colored the dynamics of human relations in social media. The culture of cancelling or boycotting someone by indulging in issues or disgrace of other parties whose truth is not yet clear is certainly problematic in today’s digital ethical world. F. Budi Hardiman pays attention to the ethics of “Click” as a moral action that needs to be explored by humans in today’s digital world. The purpose of this research is to explore the cancel culture phenomenon from the ethical perspective of “Click” and the role of Digi-sein in building morality in the digital world. The author found that “Click” has led to fanaticism and belittled value systems in the form of empathy for others. Therefore, it is necessary to have “Click” ethic that contains virtue, as described by Budi Hardiman, namely the attitude of reflective pause which refers to the act of virtue full of courage to voice the truth, honesty to convey information as it is, and self-control to refuse irrational news or opinions so that the “Click” action is filled with ethical values towards the good of life together.